Acute effect of school-based active breaks on physical activity level and on-task classroom behavior in primary schoolchildren - Reyes-Amigo, Tomás; Grao-Cruces, Alberto; Sanchez-Oliva, David; Garcia-Hermoso, Antonio; Reyes-Molina, Daniel; Yañez-Sepúlveda, Rodrigo; Olivares-Arancibia, Jorge; Hurtado-Almonácid, Juan; Páez-Herrera, Jacqueline; Salinas-Gallardo, Gabriel; Mendoza, Edgardo; Ovalle-Fernández, Camilo; et al. (Frontiers in Public Health, 2025)
IntroductionActive breaks (ABs) in the classroom are a promising way to promote children’s active behaviors while contributing to the development of their physical, academic, and cognitive skills. However, the effects of ABs, which are exclusive to classroom settings, remain unclear. The aim of this study was to determine the acute effect of an ABs intervention on physical activity levels and on-task classroom behavior in schoolchildren.MethodThe participants included 55 primary schoolchildren aged between 10 and 11 years (10.48 ± 0.5 years). Children were randomized into an experimental group (EG) and a control group (CG). In the EG, six ABs of 4 min and 30 s were applied during the school day. The CG followed their regular school day. Physical activity levels were assessed throughout the school day using accelerometers (ActiGraph wGT3X-BT, Ametris, United States), and on-task classroom behavior was evaluated using the Direct Behavior Rating Scale.ResultsThe EG showed significant differences in the min of physical activity level across all five levels compared to the CG: Sedentary time was significantly lower in the EG [EG 229.83 ± 17.17 vs. CG 253.76 ± 12.81 min, p = 0.001; effect size (ES) = −158], while light physical activity level (EG 36.65 ± 11.66 vs. CG 32.20 ± 7.77 min, p = 0.002; ES = 1.04), moderate physical activity level (EG 8.78 ± 2.98 vs. CG 7.11 ± 1.81 min, p = 0.002; ES = 1.05), vigorous physical activity level (EG 14.76 ± 4.83 vs. CG 6.52 ± 3.23 min, p = 0.001; ES = 2.64), and moderate-vigorous physical activity level (EG 23.53 ± 7.12 vs. CG 13.71 ± 4.7 min, p = 0.001; ES = 2.18) were all significantly higher. Regarding on-task classroom behavior outcomes, both academic engagement (67.51% ± 25.61 vs. 82.91% ± 18.81; p = 0.002; ES = 0.1) and disruption (15.81 ± 17.21% vs. 7.51% ± 14.81 p = 0.002; ES = 0.5) showed statistically significant differences before and after the ABs. Regarding respectfulness (84.21% ± 17.41 vs. 90.41% ± 14; p = 0.21), the ABs showed no significant changes.ConclusionABs are an effective strategy to acutely increase primary school children’s moderate and vigorous physical activity engagement and improve on-task classroom behavior. Implementation should be considered by policymakers, educators, and health professionals.Clinical trial registrationClinicalTrials.gov, identifier NCT05403996.